2019
DOI: 10.1007/s42729-019-00117-9
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil

Abstract: This study was purposely designed to evaluate the potential of faba bean (Vicia faba) residues as green manure in a maize-faba bean rotation system. Seed germination test and pot experiments were conducted to measure the effects of aqueous extract on maize seed germination and the effects of residues on crop growth and soil microbial activities. Litterbag experiment was conducted to analyze the decomposition patterns of faba bean residues during maize growing season in a regosol soil. The faba bean was separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, He et al (2020) found that corn seed germination and the lengths of radicle and plumule were lower than those of the control, particularly with 1% faba bean aqueous extract concentrations. Moreover, incorporating faba bean as green manure, the aboveground biomass of corn at the heading stages was negatively reduced by the whole plant, aboveground part, and stem (He et al, 2020). Milk vetch and spring corn rotation is an important tillage system.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, He et al (2020) found that corn seed germination and the lengths of radicle and plumule were lower than those of the control, particularly with 1% faba bean aqueous extract concentrations. Moreover, incorporating faba bean as green manure, the aboveground biomass of corn at the heading stages was negatively reduced by the whole plant, aboveground part, and stem (He et al, 2020). Milk vetch and spring corn rotation is an important tillage system.…”
Section: Introductionmentioning
confidence: 79%
“…Researchers based their findings on field tests that faba bean (Vicia faba L.) could exert weed control when used as green manure, and the weed inhibition ability was highest at the time of faba bean incorporation into the field (Álvarez-Iglesias et al, 2018). However, He et al (2020) found that corn seed germination and the lengths of radicle and plumule were lower than those of the control, particularly with 1% faba bean aqueous extract concentrations. Moreover, incorporating faba bean as green manure, the aboveground biomass of corn at the heading stages was negatively reduced by the whole plant, aboveground part, and stem (He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbes degraded phenolic acids and the released organic carbon was transformed into MBC. The progress was finished within a couple of days or 5 weeks according to the previous reports [4,36]. On the other hand, HPA/HBA addition caused some beneficial microbes to disappear such as Chaetomium, which could affect the biological nitrogen fixation and soil nutrient decrease.…”
Section: Discussionmentioning
confidence: 75%
“…Allelopathy directly influences the growth of surrounding plants ( Schalchli et al., 2012 ; He et al., 2019 ). Phenolics and their derivatives, terpenoids, and alkaloids are the main categories of plant allelochemicals ( Qu and Wang, 2008 ; Li et al., 2010 ; Lupini et al., 2018 ; Wang et al., 2018 ), which are released through different means, such as in root exudate, volatiles from leaves, and through decomposition products ( Li et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%